Biology, chemistry and applications of apocarotenoids - Ramamoorthy, Siva; Madrid, Renata Rivera; Doss, C. George Priya (Boca Raton, FL : CRC Press, 2020)
"Carotenoids are a large class of isoprenoid pigments produced by plants and certain microbes. More than 700 naturally occurring carotenoids have been identified. Apocarotenoids are tailored from carotenoids by oxidative enzymes. Apocarotenoids act as visual or volatile signals to attract pollinating and seed dispersal agents. They are also the key players in allelopathic interactions and plant defense. Biology, Chemistry and Applications of Apocarotenoids provides detailed account of the fundamental chemistry of apocarotenoids and the basic methods used in carotenoid research, and critical discussions of the biochemistry, functions, and applications of these important compounds. Topics covered in the proposed book include various aspects of the roles of apocarotenoids in colour and colouration, photosynthesis and other photofunctions and protection. The formation and roles of carotenoid metabolites and breakdown products as perfume/aroma compounds are also be outlined. Features: Provides an organized overview of apocarotenoids and their chemistry and biological functions Focuses on recent discoveries on apocarotenoids, their nature and functions. Details potential uses of apocarotenoids in agriculture, pharmacy, food industry, and apocarotenoid production at industrial level This book has been written by leading experts in apocarotenoid research and gives a comprehensive overview on the diversity of apocarotenoid compounds and would serve as a reference book for researches in Plant Physiology, Molecular Biology, Biochemistry, Biophysics and Medicine"--
Biology and Chemistry of Apocarotenoids / Margarita Aguilar-Espinosa, Victor Manuel Carballo-Uicab and Renata Rivera-Madrid -- Natural Sources of Apocarotenoids and its Applications / Dzib-Cauich Jonathan, Us-Camas Rosa and Renata Rivera Madrid -- Overview: Apocarotenoid Molecules are Continuously Being Discovered in All Taxa / Renata Rivera-Madrid and Siva Ramamoorthy -- Unraveling Apocarotenoid Biosynthesis Pathways: Transcriptomic Tools for Gene Discovery / David Chan-Rodriguez and Renata Rivera-Madrid -- Apocarotenoids: Natural Anti-Ageing Agents / Leepica Kapoor and Siva Ramamoorthy -- An Approach to Vitamin A and Retinoids and Their Importance in Human Health / Victor Manuel Carballo Uicab, Rosa Us Camas and Renata Rivera Madrid -- Epoxy Carotenoid and Its Importance: A Review / Hebron Kirubai Raj and Siva Ramamoorthy -- Anticarcinogenic Effect of Apocarotenoids / Yair Cárdenas-Conejo and Edith E. Uresti-Rivera -- An Overview of the Role of Abscisic Acid (ABA): from Plants to Humans / Us-Camas Rosa, Aguilar-Espinosa Margarita and Renata Rivera Madrid -- C13 Alpha-Ionol (Blumenol) Glycosides and C14 Mycorradicin: Apocarotenoids Accumulating in Roots During the Arbuscular Mycorrhizal Symbiosis / Michael H. Walter -- Strigolactones: Nutrient Stress Hormones Affecting Plant Development and Biotic Interactions / Michael H. Walter.
OCLC-licensed vendor bibliographic record.
Keywords: Carotenoids; Carotenoids -- Biotechnology; Carotenoids -- Health aspects; Carotenoids -- Analysis; MEDICAL / Biochemistry; MEDICAL / Biotechnology; SCIENCE / Life Sciences / Botany